Immigrant selection and short-term labour market outcomes by visa category - Abdurrahman Aydemir (Institute for the Study of Labor (IZA), 2010)
This paper studies the efficacy of immigrant selection based on skill requirements in the Canadian context. The point system results in a much higher skill level than would otherwise be achieved by family preferences. This positive selection is achieved by directly selecting higher skilled principal applicants who are assessed by the point system and also indirectly through higher skilled spouses. However, due to difficulties in transfer of foreign human capital immigrants admitted for their skills do not necessarily perform better in the labour market and important factors used to assess admissibility have very limited power to predict short-term labour market success.
Keywords: J61; J68; 330; Immigration; point system; visa category; Einwanderungsrecht; Qualifikation; Migranten; Humankapital; Berufliche Integration; Kanada